CLEAN-LABEL PRESERVATION OF APPLE SLICES BY APPLYING AQUEOUS SUMAC EXTRACT: ANTIFUNGAL AND ANTIBROWNING ACTIVITIES - Salim, Saja A; AL-abbasy, Omar Y; Sadoon, Ahmed M (Food and Feed Research, 2026)
Spoilage of food, particularly fruits like apples, is a global problem that causes economic losses and public health concerns. Fungal contamination and enzymatic browning are two main causes of spoilage. Aqueous sumac extract (ASE) as a natural inhibitor against the growth of Aspergillus flavus and enzymatic browning induced by polyphenol oxidase (PPO) in apples was investigated in this study. Iraqi sumac (Rhuscoriaria L.) fruits were treated to obtain oil and aqueous extracts, and the phytochemical composition was analyzed by Soxhlet extraction and high-performance liquid chromatography (HPLC). The aqueous extract contained phenolic compounds, including gallic acid and ferulic acid, which are known for their antioxidant and antimicrobial properties. Antifungal assays indicated that only ASE (10%) inhibited A. flavus growth, whereas oil extracts proved to be non-inhibitory. Molecular identification and DNA sequencing confirmed the fungal isolate to be A. flavus. Apple slices treated with 5% and 10% aqueous extracts were monitored for 15 days at 4°C to assess the inhibition of browning. Spectrophotometric analysis revealed that browning intensity and PPO activity decrease in a concentration-dependent manner. At the same time, there was enhanced retention of total phenolic content in treated samples, especially at the 10% level. The results demonstrate that ASE, especially at higher concentrations, effectively suppresses fungal infestation and mitigates enzymatic browning in apples. The study identifies sumac as a natural, safe preservative with the potential to boost shelf life and quality of fresh fruits and vegetables.
Keywords: Rhus coriaria; Aspergillus flavus; enzymatic browning; polyphenol oxidase; natural preservatives; shelf life